2018
DOI: 10.1016/j.ijdevneu.2018.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Adult rat morphine exposure changes morphine preference, anxiety, and the brain expression of dopamine receptors in male offspring

Abstract: Addiction to drugs, including opioids is the result of an interplay between environmental and genetic factors. It has been shown that the progeny of addict people is at higher risk for drug addiction. However, the mechanisms of such trans-generational effects of drugs are not so clear. Here we have evaluated the effects of parental morphine consumption on anxiety, morphine preference, and mRNA expression of dopamine receptors in F1 and F2 male offspring. Morphine was chronically administered to adult male and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 66 publications
2
10
0
Order By: Relevance
“…Interestingly, similar to our results of increased anxiety-like/compulsive-like behavior in offspring from morphine-exposed dams, male offspring from morphine-exposed parents displayed decreased percent open arm time in the EPM (Sabzevari et al, 2019;Vousooghi et al, 2018), increased grooming, and increased marbles buried (Rohbani et al, 2019), suggesting increased anxiety-like/compulsive-like behavior. Together with our results, these data suggest increased behavioral vulnerability in male offspring from morphine-exposed dams, while there are no apparent changes in female offspring behavior.…”
Section: -Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Interestingly, similar to our results of increased anxiety-like/compulsive-like behavior in offspring from morphine-exposed dams, male offspring from morphine-exposed parents displayed decreased percent open arm time in the EPM (Sabzevari et al, 2019;Vousooghi et al, 2018), increased grooming, and increased marbles buried (Rohbani et al, 2019), suggesting increased anxiety-like/compulsive-like behavior. Together with our results, these data suggest increased behavioral vulnerability in male offspring from morphine-exposed dams, while there are no apparent changes in female offspring behavior.…”
Section: -Discussionsupporting
confidence: 89%
“…Contrary to what we found, a few preclinical studies investigating the effects of prenatal morphine exposure found either decreased anxiety-like behavior or no changes in anxiety-related behaviors, which highlights how duration and dose of maternal morphine exposure can have seemingly opposite effects in offspring (Klausz et al, 2011; Tan et al, 2015). Interestingly, similar to our results of increased anxiety-like/compulsive-like behavior in offspring from morphine-exposed dams, male offspring from morphine-exposed parents displayed decreased percent open arm time in the EPM (Sabzevari et al, 2019; Vousooghi et al, 2018), increased grooming, and increased marbles buried (Rohbani et al, 2019), suggesting increased anxiety-like/compulsive-like behavior. Together with our results, these data suggest increased behavioral vulnerability in male offspring from morphine-exposed dams, while there are no apparent changes in female offspring behavior.…”
Section: Discussionsupporting
confidence: 89%
“…Although earlier opioid exposure certainly increases the length of experiments which can be burdensome, pregestational opioid exposure can impact offspring development and behavior. Opioid treatment prior to conception (but not gestational exposure) has been shown to alter the dopaminergic system, morphine preference, and morphine analgesia sensitivity in offspring likely through epigenetic mechanisms (Byrnes et al, 2011;Byrnes et al, 2013;Vousooghi et al, 2018;Sadat-Shirazi et al, 2019). As previously stated, this represents another area where the translational value of animal models could be improved as most women using opioids begin doing so prior to pregnancy.…”
mentioning
confidence: 91%
“…Furthermore, F1 male progeny of morphine-exposed parents had a greater preference for morphine and more anxiety-like behavior; these effects were not seen in the F2 generation [75]. F1 male progeny also exhibited increased expression of D1 and D5 dopamine receptors in the PFC and NAc; D5 and D2 receptors were decreased in the hippocampus.…”
Section: Morphinementioning
confidence: 92%
“…F1 male progeny also exhibited increased expression of D1 and D5 dopamine receptors in the PFC and NAc; D5 and D2 receptors were decreased in the hippocampus. The D4 dopamine receptor was augmented in striatum and hippocampus and decreased in the PFC [75]. Alterations in dopamine receptor expression within the reward system may be one mechanism responsible for these behavioral changes in F1 offspring.…”
Section: Morphinementioning
confidence: 97%